2013
DOI: 10.23939/chcht07.04.397
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Studies of Some Thiazolo[4,5-b]pyridines as Novel Antioxidant Agents: Enhancement of Activity by Some Molecular Structure Parameters

Abstract: The antioxidant activity of novel N 3 and C 6 substituted 5,7-dimethyl-3H-thiazolo [4,5-b]pyridine-2one derivatives was evaluated in vitro by the method of scavenging effect on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. The correlation analysis between the antioxidant activity and different subsets molecular descriptors was carried out for 19 compounds. The regression models derived with QSAR-analysis display the significant influence of topological structure, atom and bond type counts, physicochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…For thiazolo[4,5‐ b ]pyridines derivatives were also shown to possess strong inhibitory actions for Ab42 fibrillization at the micromolar level for Alzheimer disease treatment . The significant antiexudative, antimicrobial, and antioxidant effects of some thiazolo[4,5‐ b ]pyridine derivatives had been also reported . Some of their analogues were known as H3 receptor antagonists or act as antagonists of metabotropic glutamate receptors 5 (mGluR5) while others were showed as potent inhibitors with respect to the receptors of the epidermal growth factor .…”
Section: Introductionmentioning
confidence: 99%
“…For thiazolo[4,5‐ b ]pyridines derivatives were also shown to possess strong inhibitory actions for Ab42 fibrillization at the micromolar level for Alzheimer disease treatment . The significant antiexudative, antimicrobial, and antioxidant effects of some thiazolo[4,5‐ b ]pyridine derivatives had been also reported . Some of their analogues were known as H3 receptor antagonists or act as antagonists of metabotropic glutamate receptors 5 (mGluR5) while others were showed as potent inhibitors with respect to the receptors of the epidermal growth factor .…”
Section: Introductionmentioning
confidence: 99%
“…They also show potent Ab 42 fibrillization inhibitory activities in Alzheimer's disease treatment (Lee et al 2008). Among this type of substances, several compounds were found to possess fungicidal (Marzoog and Al-Thebeiti 1978), anti-inflammatory (Chaban et al 2016(Chaban et al , 2017b(Chaban et al , 2018b(Chaban et al , 2019a, tuberculostatic (Chaban et al 2014), antioxidant (Chaban et al 2013;Klenina et al 2013Klenina et al , 2017 and antitumor effects (Chaban et al 2012a). Some of them are H3 receptor antagonists (Walczyn´ski et al 2005), or act as antagonists of metabotropic glutamate receptors 5 (mGluR5) (Lin et al 2009), they are of high inhibitory activity with respect to the receptors of the epidermal growth factor (Komoriya et al 2006), and were revealed to activate the GK enzyme in vitro and significantly reduces glucose levels (Singh et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Thiazolo [4,5-b]pyridines were also shown to possess strong inhibitory actions for Aβ42 fibrillization at the micromolar level for Alzheimer's disease treatment [2]. The significant antiexudative, antimicrobial and antioxidant effects of some thiazolo [4,5-b]pyridine derivatives had been also reported [3][4][5][6][7][8]. Some of their analogues were recognized as H3 receptor antagonists [9,10] or act as antagonists of metabotropic glutamate receptors 5 (mGluR5) [11] while other were revealed as potent inhibitors with respect to the receptors of the epidermal growth factor [12].…”
Section: Introductionmentioning
confidence: 99%